THE ESSENCE OF FREELANCE ACTIVITY, CHARACTERISTICS OF ITS DEVELOPMENT - Lutpiddinov Shukhratjon Zakirjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides information on freelancing activities and develops new ways of developing freelancing in the context of Industry 4.0.